1997
DOI: 10.1108/00368799710165747
|View full text |Cite
|
Sign up to set email alerts
|

Oil ageing ‐ drain period in a petrol engine

Abstract: The authors wish to thank Shell Oil Company for providing test facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 5 publications
(3 reference statements)
1
17
0
Order By: Relevance
“…Kinematic viscosity ν (Figure 10) of the thermally degraded oil in this study varied linearly with ageing time, due to the buildup of insolubles and evaporative loss of more volatile components observed by Kaleli and Yavslioli [24]. This variation pattern of viscosity with ageing agrees with the results of Singh et al [25].…”
Section: Viscosity and Total Acid Number (Tan)supporting
confidence: 88%
“…Kinematic viscosity ν (Figure 10) of the thermally degraded oil in this study varied linearly with ageing time, due to the buildup of insolubles and evaporative loss of more volatile components observed by Kaleli and Yavslioli [24]. This variation pattern of viscosity with ageing agrees with the results of Singh et al [25].…”
Section: Viscosity and Total Acid Number (Tan)supporting
confidence: 88%
“…As a result, current engine lubricants used in internal combustion engines (ICE) are responsible for reducing engine friction losses and contact wear. Therefore, the impact of engine oil viscosity and aging is of prime interest with regard to the motion of passenger cars [20]. Several methods were presented and discussed in the open literature to study the variation of lubricant viscosity and oil degradation over time.…”
Section: Introductionmentioning
confidence: 99%
“…According to Coates and Setti (1986), the maximum permissible changes (increasing or decreasing) in viscosity is 25%. An increase in viscosity is caused by contamination, nitration, or oxidation, whereas a decrease in viscosity occurs when the amount of fuel in the oil increases (Kaleli and Yavasliol, 1997). Temperature has a direct effect on the oil viscosity.…”
Section: Kinematic Viscositymentioning
confidence: 99%
“…They rotated the viscometer in accordance with the American Society for Testing and Materials (ASTM) D445 stipulations, and their results showed that the temperature is inversely correlated with viscosity; therefore, any decrease in the temperature will increase the engine oil viscosity. In addition, in the study by Kaleli and Yavasliol (1997), an SAE viscosity grade of 20W-50 was used in 2 different engines. The results showed that after 15,000 km, the viscosity of the oil used in the second engine decreased at 40℃ from 160.16 cSt to 103.02 cSt, and at 100℃ the viscosity of the oil decreased from 18.09 cSt to 13.24 cSt.…”
Section: Kinematic Viscositymentioning
confidence: 99%
See 1 more Smart Citation